DWARF WITH SLENDER LEAF1 Encoding a Histone Deacetylase Plays Diverse Roles in Rice Development. (7th November 2019) - Kubo, Fumika Clara; Yasui, Yukiko; Ohmori, Yoshihiro; Kumamaru, Toshihiro; Tanaka, Wakana; Hirano, Hiro-Yuki
Abstract: In plants, reversible histone acetylation and deacetylation play a crucial role in various biological activities, including development and the response to environmental stress. Histone deacetylation, which is generally associated with gene silencing, is catalyzed by multiple histone deacetylases (HDACs). Our understanding of HDAC function in plant development has accumulated from molecular genetic studies in Arabidopsis thaliana . By contrast, how HDACs contribute to the development of rice ( Oryza sativa ) is poorly understood and no rice mutants of HDAC have been reported. Here we have characterized a new rice mutant showing semi-dwarfism, which we named dwarf with slender leaf1 ( dsl1 ). The mutant showed pleiotropic defects in both vegetative and reproductive developments; e.g. dsl1 produced short and narrow leaves, accompanied by a reduction in the number and size of vascular bundles. The semi-dwarf phenotype was due to suppression of the elongation of some culm (stem) internodes. Interestingly, despite this suppression of the upper internodes, the elongation and generation of lower internodes were slightly enhanced. Inflorescence and spikelet development were also affected by the dsl1 mutation. Some of the observed morphological defects were related to a reduction in cell numbers, in addition to reduced cell division in leaf primordia revealed by in situ hybridization analysis, suggesting the possibility that DSL1 is involved in cell division control. Gene cloning revealed that DSL1 encodes an HDAC belonging to the reduced potassium dependence3/histone deacetylase1 family. Collectively, our study shows that the HDAC DSL1 plays diverse and important roles in development in rice.